LATIHAN FISIK PADA FRAILTY SYNDROME - Gessal, Joudy; Utari, Widya (Jurnal Biomedik : JBM, 2013)
Abstract: Frailty Syndrome (FS) is a geriatric syndrome characterized by decreases of functional ability and adaptation due to multi-system functional degradation, and an increase of susceptibility to a variety of pressures, resulting in a decrease of functional performance and health status. FS occurs in 30% people over 80 years and in 7% over 65 years. The incidences of FS in females were higher than in males due to the females’ smaller/lower/less body mass; therefore, loss of muscle mass due to aging process is faster. Anorexia, sarcopenia, immobilization, atherosclerosis, balance disorder, depression, and cognitive disorders are conditions that can lead to the occurences of FS. Although FS increases the morbidity and accelerates the mortality, the right type of exercise can overcome this syndrome and improves the quality of life. Keywords: Frailty syndrome, geriatric, quality of life. Abstrak: Frailty Syndrome (FS) adalah suatu sindroma geriatrik dengan karakteristik berkurangnya kemampuan fungsional dan fungsi adaptasi yang diakibatkan oleh degradasi fungsi berbagai sistem dalam tubuh, serta meningkatnya kerentanan terhadap berbagai macam tekanan; kesemuanya ini menurunkan performa fungsional dan status kesehatan seseorang. Frailty Syndrome terjadi pada 30% populasi di atas usia 80 tahun dan 7% pada populasi usia di atas 65 tahun. Insiden pada perempuan lebih tinggi oleh karena perempuan memiliki massa tubuh yang lebih kecil daripada laki-laki sehingga kehilangan massa otot lebih cepat terjadi pada proses aging. Anoreksia, sarkopenia, imobilisasi, aterosklerosis, gangguan keseimbangan, depresi dan gangguan kognitif merupakan kondisi-kondisi yang dapat menyebabkan terjadinya FS. Walaupun FS menyebabkan peningkatan morbiditas dan percepatan terjadinya mortalitas, latihan yang tepat dapat mengatasi sindroma dan meningkatkan kualitas hidup. Kata kunci: frailty Syndrome, geriatrik, kualitas hidup.